Construct Validity of the Multi-Source Interference Task to Examine Attention in Heart Failure. Issue 6 (November 2018) - Jung, Miyeon; Jonides, John; Berman, Marc G.; Northouse, Laurel; Koelling, Todd M.; Pressler, Susan J.
Abstract : Background: Patients with heart failure (HF) are at risk of cognitive dysfunction, including decreased directed attention. Directed attention is critical for performing daily activities including HF self-care by facilitating one to follow instructions or train-of-thought when there are interferences in which presented stimuli are in conflict with one another. The Multi-Source Interference Task (MSIT) is a computerized neuropsychological test that examines the function of the dorsal anterior cingulate cortex, the neurological substrate for directed attention. However, the MSIT has not been used in past HF studies. Objective: The purpose of the study was to examine construct validity of the MSIT in HF. Methods: Baseline data were obtained from a cognitive intervention study among patients with HF ( n = 22) and age- and education-matched healthy adults ( n = 20). Construct validity was evaluated using t tests to examine differences between patients with HF and healthy adults and congruent and incongruent MSIT trials. Pearson's correlations were computed to examine relationships between the MSIT and Trail-Making Test, Stroop Test, and Attentional Function Index. Results: Compared with healthy adults, patients with HF demonstrated worse performance (i.e., slower response times and higher error rates) on MSIT. Patients with HF had worse performance on MSIT incongruent trials than congruent trials. Interference z scores of MSIT did not correlate with Trail-Making Tests A and B and Stroop Test interference z scores, but the MSIT interference z scores correlated with perceived attention function measured by Attentional Function Index. Discussion: Construct validity of the MSIT was supported, in part, among patients with HF. The MSIT is a sensitive measure of detecting worse directed attention among patients with HF compared with healthy adults. The preliminary findings support the use of the MSIT as a measure of directed attention in HF. Confirmation is warranted for current findings in larger samples.